Penerimaan diri wanita hamil dengan HIV positif - Putri, Anggie Pradana; AM, Adi Irawan; Padua, Marlene R (Riset Informasi Kesehatan; Vol 10 No 1 (2021)DO - 10.30644/rik.v10i1.425, 2021)
Background : Being HIV positive, someone will face psychological pressure such as depression, anxiety and other negative ones. Pregnant women with HIV positive face two challenges, to keep her pregnancy and struggle to fight with HIV. Self-acceptance of those two dimensions gives high challenges for pregnant women who are HIV positive. The aim of the study is to understand deeper and describe about the self-acceptance of pregnant women with HIV positive Method : This study used qualitative research method with phenomenology approach. The participants are the pregnant women with HIV positive with inclusion criteria as: 1) woman in reproductive age 18-40 years old, 2) confirmed pregnant, 3) natural born of Indonesia, 4) can expressed her-selves verbally. The data analyzed with Collaizi’s analysis of qualitative research. Results : Data saturation was reached on the seventh participant. From the qualitative data analysis, there are three themes under the phenomenon of self-acceptance of pregnant-women with HIV positive, such as internal negativism, internal acceptance, and ready to enhanced health status. Conclusion : The process of self acceptance of being pregnant and infected with HIV gives contribution on the continuity of antenatal care and HIV therapy in order to the improvement of quality of life. Self-denial depicts as disappoint, anxiety, unbelief, blame herself, isolate her self, become as consequences of the situation. But, due to the support from family and people around, makes the pregnant mothers with HIV positive try to accept and disclose about her status. So, it will give better self-acceptance of to improve her health